Modelling the early development of cartilage and bone in Mseleni Joint Disease using induced pluripotent stem cells - Mkatazo, Thulisa (Department of Human Biology, 2025)
Mseleni joint disease (MJD) is an unusual crippling osteoarthropathy that occurs in significant numbers of the indigenous population in a remote rural region of Northern KwaZulu Natal, South Africa. The most affected joints are the hip, and early developmental abnormalities lead to secondary osteoarthropathy. Autoradiographs show irregularities and fragmentation of the joint epiphyses in the early stage of MJD. Over time, erosion of the articular cartilage leads to fibrillation and flaking that ultimately exposes the bone. Despite extensive epidemiological, anthropological and genetic investigations, and studies on the local environment, diet and mineral deficiencies, the cause of MJD is still unknown. The present study is built on the hypothesis that there are abnormalities in early joint cartilage and bone development, leading to functional abnormalities, which over time result in early onset arthritis. The aim of the present study is to create an in vitro model of embryonic cartilage and bone to determine whether there are intrinsic disturbances in the early differentiation of these tissues. This study is part of a collaboration with Prof V. Gibbon (HREC: 822/2015). Skin fibroblasts from two MJD patients, one unaffected person from Mseleni and one unaffected non-Mseleni control, were reprogrammed into induced pluripotent cells (iPSC) by a collaborator. Pluripotency was confirmed by (qRT-PCR) gene expression analysis of the reprogramming genes OCT3/4, NANOG and SOX2 and immunocytochemical staining for their proteins. In vitro differentiation into the three germ layers was confirmed by ICC. To generate iPSC-derived mesenchymal stem cells (iMSC) from the iPSCs, two differentiation protocols were tested: one with low glucose medium and one with standard glucose medium. Changes in the morphology, growth characteristics and expression of relevant CD markers were determined. The mesenchymal phenotype was confirmed by the positive qRT-PCR expression of CD73, 105 and 90. Induced MSC from one MJD and one control cell line were differentiated into adipose, bone and cartilage tissues. Two specific differentiation media were used for each specific tissue type. The first medium included basal medium supplemented with the reagents and chemicals appropriate for the particular tissue type (adipose, bone or cartilage). The second medium was the commercially available StemPro™ differentiation medium specific for either adipogenesis or osteogenesis or chondrogenesis. The trilineage differentiation was monitored by qRT-PCR and tissue specific stains. Oil Red O staining revealed differentiation into adipose phenotype. Alizarin Red staining and qRT-PCR for Osteocalcin and Alkaline Phosphatase confirmed the presence of bone tissues in cells cultured in both media types. For chrondrogenic differentiation, cells were grown as micro-masses which were harvested and stained with toluidine blue. Only the experiments using the commercial StemPro™ kit were positive for chondrogenesis. To determine what type of cartilage had been produced (articular or endochondral hypertrophic) in these experiments, chondrogenic micromasses were removed for gene expression analysis at various intervals over a 21-day period. qRT-PCR analyses revealed the presence of both COL2A1 and COL10A1, gene markers typical of hypertrophic cartilage. In conclusion, the results of this study indicate that both the MJD and control iMSC cell lines were able to differentiate along adipogenic, chondrogenic and osteogenic pathways. The chondrogenic cells had differentiated into hypertrophic endochondral cartilage. A different culture approach would be needed to develop a protocol for differentiation into an articular cartilage phenotype which would, in turn, facilitate a further study for potential intrinsic disturbances underlying MJD.